2004
DOI: 10.2138/gsrmg.55.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the Understanding and Application of Lithium Isotopes in the Earth and Planetary Sciences

Abstract: INTRODUCTIONThe signifi cant relative mass difference (c. 16%) between the two stable isotopes of Li (approximately 6 Li 7.5%, 7 Li 92.5%), coupled with broad elemental dispersion in Earth and planetary materials, makes this a system of considerable interest in fi ngerprinting geochemical processes, determining mass balances, and in thermometry. Natural mass fractionation in this system is responsible for c. 6% variation among materials examined to date ( Fig. 1). Although the "modern era" of Li isotope quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
152
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(167 citation statements)
references
References 140 publications
(268 reference statements)
12
152
1
2
Order By: Relevance
“…The accuracy and the reproducibility of the procedure for solid samples (dissolution + 172 purification procedure + mass analysis) were tested by repeated measurement of the JB-2 173 basalt standard (Geological Survey of Japan), giving a mean value of δ 7 Li = +4.9‰ ± 0.6 (2σ, 174 n=17) which is in good agreement with published values (see Carignan et al, 2007, and 175 Tomascak, 2004, for data compilation). Consequently, based on long-term measurements of 176 both seawater and JB-2 basalt standards, we estimate the external reproducibility of our 177 method to be around ± 0.5‰ (2 σ).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The accuracy and the reproducibility of the procedure for solid samples (dissolution + 172 purification procedure + mass analysis) were tested by repeated measurement of the JB-2 173 basalt standard (Geological Survey of Japan), giving a mean value of δ 7 Li = +4.9‰ ± 0.6 (2σ, 174 n=17) which is in good agreement with published values (see Carignan et al, 2007, and 175 Tomascak, 2004, for data compilation). Consequently, based on long-term measurements of 176 both seawater and JB-2 basalt standards, we estimate the external reproducibility of our 177 method to be around ± 0.5‰ (2 σ).…”
supporting
confidence: 72%
“…The relative mass difference between the two isotopes is 56 considerable at 17%, generating significant mass-dependant fractionation during geochemical 57 processes. The range of variation in lithium-isotope compositions is more than 50‰ in 58 geological materials (see Coplen et al, 2002;Tomascak, 2004 for data compilation). As Li is 59 3 a recently developed isotopic tracer, not all the processes that could induce and control 60 isotopic fractionation are as yet well constrained.…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium is mobile in hydrous fluids and there is a strong isotopic fractionation between its two stable isotopes at low temperatures due to the large relative mass difference (~16%) (Tomascak, 2004). Recent studies demonstrated that the Li isotope system is very sensitive to metasomatic enrichment processes (Marschall et al, 2009;Penniston-Dorland et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The relative mass difference between the two isotopes is considerable (17%) and is likely to generate large mass dependent fractionation during geochemical processes, even at high temperature. The range of variation in Li isotopic compositions is more than 50‰ in geological materials (Coplen et al, 2002;Tomascak, 2004).…”
Section: Introductionmentioning
confidence: 99%